Case Report: Symptomatic Chronic Granulomatous Disease in the Newborn - Miladinovic, Milica; Wittekindt, Boris; Fischer, Sebastian; Gradhand, Elise; Kunzmann, Steffen; Zimmermann, Stefanie Y.; Bakhtiar, Shahrzad; Klingebiel, Thomas; Schlösser, Rolf; Lehrnbecher, Thomas (Frontiers in Immunology, 2021)
Chronic granulomatous disease (CGD) is a primary immunodeficiency, which is diagnosed in most patients between one and three years of age. Here we report on a boy who presented at birth with extensive skin lesions and lymphadenopathy which were caused by CGD. An analysis of the literature revealed 22 patients with CGD who became symptomatic during the first six weeks of life. Although pulmonary complications and skin lesions due to infection were the leading symptoms, clinical features were extremely heterogenous. As follow-up was not well specified in most patients, the long-term prognosis of children with very early onset of CGD remains unknown.